Legion of super heroes. Volume 1 [videorecording (DVD)] / Kids WB. (Warner Home Video, 2007)
Superheroes from the 31st century head back in time to enlist Superman's help in battling their nemeses, the Fatal Five. But when they arrive he is an introverted young adult whose abilities need fine-tuning and doesn't even know he's a superhero.